Conversion of pastures to oil palm plantations in Colombia generates lower greenhouse gas emissions than cattle ranching: a literature research - Gómez Mateus, Adriana Marcela; Grimm, Lucas; Waldhardt, Rainer; Justus Liebig University Giessen (My University, 2021)
We conduct a literature research to compare GHG emissions between oil palm plantations and cattle ranching, two of the most common land uses in eastern Colombia. Our results show that conversion of pastures to oil palm plantations or cattle ranching generates greenhouse gas emissions (GHG). Oil palm cultivation generates lower GHG emissions than cattle ranching. Oil palms can stock high amounts of carbon and alternate uses of organic waste (e.g., composting, energy generation) lead to carbon sequestration and even to carbon savings. The establishment of oil palm plantations in eastern Colombia might mitigate the effects of global warming due to the creation of a carbon stock. The availability of pastures in Colombia offers an opportunity to minimize the impacts of future oil palm expansion. However, further studies are needed to understand the GHG emissions, carbon savings, and carbon stock values in the region, from the palm oil plantations and cattle ranching. In addition to its climatic performance, attention should be paid to how the land use change could improve sustainable production, and whether oil palm plantations or cattle ranching, in eastern Colombia, can contribute to both social and environmental factors.
Keywords: greenhouse gas emissions (GHG); oil palm plantations; cattle ranching; land use change; ddc:333.7; ddc:630